Modelling carbon cycling through phytoplankton and microbes in the Scotia-Weddell Sea area during sea ice retreat - Lancelot, Christiane; Billen, Gilles; Veth, Cornelis; Becquevort, Sylvie; Mathot, Sylvie (1991)
An ecological model to calculate phytoplankton development and microbial loop dynamics in the marginal ice zone of the antarctic ecosystem has been established on the basis of physical and biological (phyto- and bacterioplankton biomass and activity and counting of two classes of heterotrophic nanoplankton) measurements carried out in the marginal ice zone of the Scotia-Weddell Sea sector of the Southern Ocean during sea ice retreat 1988 (EPOS 1 and 2 expeditions). Application of this model at latitudes where sea ice retreat occurs and in adjacent open sea and permanently ice-covered areas demonstrated that the marginal ice zone is a region of enhanced primary and bacterioplankton production. Combining the results of the phyto- and bacterioplankton models allowed the quantitative estimate of the carbon fluxes through the lower level of the planktonic food web of the Weddell Sea marginal ice zone during the sea ice retreat period. The resulting carbon budget revealed the quantitative importance of microbial and micrograzing processes in the pathways of net primary production, 71% of this latter being assimilated in the microbial food web. However, total net microbial food web secondary production contributed 28% of‘marginal ice zone produced’ food resources available to krill and other Zooplankton. SCOPUS: NotDefined.j info:eu-repo/semantics/published